The causes of communication failure in the language classroom of form three students of Sekolah Menengah Kebangsaan Tengku Intan Zaharah, Dungun, Terengganu Darul Iman / Mohd Nasir Muda - Muda, Mohd Nasir (2002)
A great deal of current theory and research stresses the importance of providing learners with opportunities for real and meaningful communication in second language acquisition. The KBSM (Kurikulum Bersepadu Sekolah Menengah) English reflects the influence of such thinking. This study aims to investigate the following issues: first whether or not the provision of opportunities for meaningful communication in the English classroom: second what the level of learners7 confidence is in using English in class communication: and third, what factors account for different confidence levels in class communication. With regard to these questions, a questionnaire was administered to 60 Form Three students of Sekolah Menengah Kebangsaan Tengku Intan Zaharah, Dungun, Terengganu Darul Iman. The results of the study indicate, first, the persistence of non- interactive patterns of communication in the English classroom, where learners' opportunities for participating in classroom communication are limited. Second, a majority of the learners are not confident in communicating in English in the classroom. Finally, three main factors contributing to learners' confidence levels for participating in classroom communication are identified. They are a self -esteem factor, a language anxiety factor, and a factor of non -favorable patterns and opportunities for classroom communication. Within these factors, the learners' perceptions of their poor English standards and the teachers' attitude towards the learners' performance in class were found to be particularly important.